Development of a Web-Based School Payment Administration Information System Using the Laravel Framework - Arifin, Samsul; Asroni, Asroni; Kurniawati, Aprilia (Universitas Muhammadiyah Yogyakarta, 2021)
A school’s payment administration management system is crucial for its well-being because all activities require payment administration to run successfully. The administration department is responsible for managing the payment, including recording payment of Education Development Contribution (SPP) and other contribution fees and generating reports. Unfortunately, these tasks are carried out manually and have not been digitized, resulting in the possibility of erroneous data and a lengthy recording procedure. Accordingly, it necessitates developing a web-based system for school payment administration management to decrease the risk of payment and recording errors. Laravel was utilized as the application’s framework, with PHP as the language. Database management system employed MySQL. Observation, interviews, and system analysis were performed to create a web application. This application could resolve issues, making payment data recapitulation more effective and efficient while reducing the risk of data inaccuracy